Badminton injuries - a prospective epidemiological and socioeconomic study - Hoy, K.; Lindblad, B. E.; Terkelsen, C. J.; Helleland, H. E. (British Journal of Sports Medicine, 1994)
During a 1-year period 100 badminton players were registered and treated in the casualty ward of Randers City Hospital, Denmark. The injuries to the badminton players constituted 5% of all sports injuries registered during the same period in the casualty ward. At follow-up questionnaires were sent to all participants. Replies were received from 89 patients. Over the same period all sports participants in the hospital catchment area (30,254) were registered according to their sport affiliation (2620 badminton players-1650 men and 970 women). Of those injured 58% were men (mean age 31 years) and 42% were women (mean age 25 years). Of the injuries 55% occurred in club players, the remainder occurring during company and school sports activities. The active players were classified into three groups according to age: Group 1 under 18 years (31%); Group 2 18-25 years (16%); Group 3 more than 25 years (53%). According to the Abbreviated Injury Scale (AIS) 17% of the injuries were classified as minor, 56% as moderate, and 27% as severe, respectively. Of the severe injuries (AIS = 3) 56% were found in the oldest age group. AIS correlated with time absent from sport (P < 0.001). Nine players (9%) reported that earlier injuries had influenced the actual accident. Most players (96%) trained one to three times a week. Sprains were the injury most commonly diagnosed (56%), fractures accounted for 5%, torn ankle ligaments were found in 10%, and 13% had ruptures to the Achilles tendon. Overall, 21% were admitted to hospital. None of the patients treated as inpatients was kept in hospital for more than 7 days.